The Role of Al-Jarh Wa At-Ta'dil Science in Maintaining the Authenticity of the Prophet's Hadith - R. Rezeki Alam; Dadah, Dadah; Engkos Kokasih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The science of al-Jarh wa at-Ta'dil plays an important role in ensuring the authenticity of the hadiths of the Prophet Muhammad, which is the most important science in Islamic studies. This journal in depth discusses how this science is applied to filter authentic hadiths from those that are not, by focusing on evaluating the credibility of hadith narrators. Through the analysis of key concepts and the application of scientific methods in the field of al-Jarh wa at-Ta'dil, the research explores the mechanisms of assessment of the narrators and how they affect the status of validity of a hadith. The results of this research confirm that a comprehensive and in-depth understanding of the science of Jarh wa Ta'dil is not only vital in upholding the authenticity of the Prophet's hadiths, but also in maintaining the integrity and validity of hadith traditions in Islam. Thus, this science contributes significantly to efforts to preserve authentic and trusted Islamic teachings. This research also highlights the importance of knowledge and skills in the science of Jarh wa Ta'dil for Islamic researchers, scholars and scholars, and students studying hadith, as a means to understand and implement the teachings of the Prophet more accurately and responsibly.